“Sentiment Analysis of Social Media Data using Machine Learning” - Vaishali Devidas Khandagale (International Journal of Intelligent Systems and Applications in Engineering, 2025)
In today’s hyper-connected digital landscape, understanding public opinion across social platforms is critical for businesses, marketers, and researchers. Sentiment Analysis is a comprehensive web-based sentiment analysis application that aggregates and analyzes content from multiple social media platforms to provide actionable insights into public sentiment regarding specific topics, brands, or trends. The system features a Flask-based backend that seamlessly integrates with Twitter, Instagram, and Reddit through specialized scraping modules, employing advanced HTML parsing and API connectivity to gather relevant content. Sentiment analysis core analysis engine leverages the TextBlob natural language processing library to evaluate content sentiment, providing granular polarity and subjectivity metrics that categorize content as positive, negative, or neutral with high accuracy. The intuitive web interface delivers a responsive, user-friendly dashboard where users can initiate cross-platform searches using keywords or hashtags and visualize sentiment distribution through interactive charts and comprehensive data tables. Real-time sentiment updates allow for tracking opinion shifts over time, while the detailed analytics panel provides insights into engagement patterns and sentiment drivers. Sentiment Analysis implements robust user authentication through Flask-Login with secure password hashing, ensuring data privacy and personalized user experiences. The system’s modular architecture facilitates easy platform expansion and algorithm refinement, while comprehensive logging mechanisms ensure operational transparency and debugging capabilities. This tool bridges the gap between complex sentiment analysis techniques and practical business applications, empowering organizations to make data-driven decisions based on authentic social media feedback, identify emerging reputation issues, and measure campaign effectiveness across multiple platforms simultaneously.